L J,so it looks like you are dealing with systems of equations.
I'll solve it for you real quick below.
-2x- 2y = 6
y = 3x - 5
The best method to use is to solve with substitution.
Step 1:
Write the equations.
y = 3x - 5
-2x- 2y = 6
Step 2: Solve for Y in y = 3x - 5
Notice that Y is already given, which is 3x - 5,
so:
Step3:Substitute 3x - 5 for y in -2x- 2y = 6
-2x - 2y = 6
-2x - 2(3x - 5) = 6
-8x + 10 = 6
Step 4: Isolate -8x
-8x+ 10 - 10 = 6 - 10
-8x= -4
Step 5: Isolate x further by dividing by -8 on both sides
-8x / -8 = -4 / -8
x = 1/2. So no, X is not equal to 5.
We also need to solve for Y. Since we got X = 1/2, substitute 1/2 for X in either equation, preferably the original (or first) equation.
y = 3x - 5
y = 3(1/2) - 5
Simplify
y = -7/2
Therefore, x = 1/2, and y= -7/2 OR (1/2, -7/2)
-2x - 2y = 6
y = 3x -5
-2x -2(3x=17)=6
-2x-6x-34
-8x-34=6
=34=34
-8x=40
x=5
is this right?
2 answers
I didn't check the whole calculation, but
-8x=40
x=5
is certainly wrong.
You can easily check to see whether your answer is correct. Just use it! If x=5,
-2*5 - 2y = 6
-10-2y = 6
-2y = 16
y = -8
y = 3*5 -5
y = 15-5 = 10
Clearly that is not the correct value for x.
-8x=40
x=5
is certainly wrong.
You can easily check to see whether your answer is correct. Just use it! If x=5,
-2*5 - 2y = 6
-10-2y = 6
-2y = 16
y = -8
y = 3*5 -5
y = 15-5 = 10
Clearly that is not the correct value for x.